The evolving landscape of restrictive cardiomyopathy treatment: clinical trial trends and future directions - Deng, Bin; Liu, Wenhua (Frontiers in Cardiovascular Medicine, 2025)
Restrictive cardiomyopathy (RCM) is a rare form of heart muscle disease characterized predominantly by diastolic dysfunction and restrictive filling, for which no guideline-supported pharmacological treatment currently exists. We reviewed the clinical trial landscape for RCM to identify emerging therapeutic strategies and trends. Using the TrialTrove database, we identified 63 RCM-related clinical trials (2007–2024) after excluding studies of standard therapies or unrelated conditions. Our analysis shows that research interest in RCM has remained modest but steady, with many trials in early (Phase I) and late (Phase III/IV) stages. Transthyretin stabilizers, particularly tafamidis, accounted for a significant portion of these trials and have demonstrated improved cardiac function and outcomes in transthyretin amyloid cardiomyopathy (ATTR-CM). In addition, novel disease-modifying approaches – including antisense oligonucleotides, RNA interference therapies, and gene-editing strategies – are being explored in clinical trials, reflecting a shift towards targeted treatment of underlying causes. Approximately half of the identified trials have been completed, though a few were terminated early due to insufficient efficacy. These findings highlight a dynamic and evolving therapeutic landscape in RCM. While tafamidis has substantially advanced ATTR-CM management, emerging RNA-silencing and gene therapy techniques hold promise to address the unmet needs in RCM, warranting further large-scale studies to validate their safety and efficacy.